Pengaruh Suplementasi Vitamin E terhadap Efek Samping Deksametason pada Paru-Paru Tikus Putih Jantan - Ichsantya, Bina; Berata, I Ketut; Samsuri, Samsuri; Merdana, I Made (Buletin Veteriner Udayana, 2017)
Side effects of dexamethasone may occur in several organs, including the lungs. Lung damage due to dexamethasone can be reduced by antioxidants. This study aims to determine the effect of vitamin E as an antioxidant supplementation in reducing the side effects of dexamethasone on the lungs. This study used 25 male rats which divided into five groups, namely: the negative control group were given food and drink only, the positive control group were given dexamethasone subcutaneously at a dose of 0.13 mg/kg bw, group P1were  given dexamethasone subcutaneously at a dose of 0.13 mg/kg bw and vitamin E orally at a dose of 100 mg/kg bw, group P2 were  given dexamethasone subcutaneously at a dose of 0.13 mg/kg bw and vitamin E orally at a dose of 150 mg/kg bw and group P3 were given subcutaneously at a dose dexamethasone 0.13 mg/kg bw and vitamin E orally at a dose of 200 mg/kg bw respectively. After 14 days of treatment, then the rats were necropsy. The lungs were taken for histopathology preparations by Hematoxylin-Eosin (HE) staining method. The variables examined include edema, hemorrhage and inflammation. The results showed a histopathological changes in lung tissue were significantly different between the positive control group and negative control group, whereas the change towards improvement in lung tissue was not significantly different in all groups P1, P2 and P3. The conclusions of this study were the administrations of dexamethasone at dose of 0.13 mg/kg of body weight causing histopathological lesion in the lung tissue of white rats including edema, bleeding and inflammation. Supplementation of vitamin E up to dose of 200 mg/kg of body weight have not provided significant improvement healing in lung tissue of rats who were treated by dexamethasone.